2004
DOI: 10.1001/archsurg.139.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Successful Laparoscopic Splenectomy in Patients With Immune Thrombocytopenic Purpura

Abstract: Hypothesis: Younger patients with immune thrombocytopenic purpura (ITP) and high preoperative platelet counts successfully respond to laparoscopic splenectomy (LS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 37 publications
4
46
0
Order By: Relevance
“…ITP was treated surgically even up to 1958, when Damashek et.al. described the term "hypersplenism" and demonstrated the significance of GC in the treatment of chronic ITP and established it as the first line of treatment (7,14). The side -effects of GC therapy and the development of minimally invasive surgical techniques facilitated the introduction of laparoscopic splenectomy in the treatment of ITP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ITP was treated surgically even up to 1958, when Damashek et.al. described the term "hypersplenism" and demonstrated the significance of GC in the treatment of chronic ITP and established it as the first line of treatment (7,14). The side -effects of GC therapy and the development of minimally invasive surgical techniques facilitated the introduction of laparoscopic splenectomy in the treatment of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports that the type of operation does not affect the ITP outcome in a statistically significant way (5,11). One of the most frequently assessed factors, which could influence ITP outcome following an operation is age (3,7,8,14). In our study the mean value of the cured patients' age -34.6 ± 9.8 years is lower in a statistically significant way compared to those patients, who continue treatment or who have experienced transformation of the disease (F = 7.327; p = 0.011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remission index after splenectomy in case of ITP patients ranged between 64% and 90% (11)(12)(13)(14)(15)(16). In a meta-analysis, Kojouri and co-authors (135 investigations during the period between 1996 and 2004) examined the effect of splenectomy in patients with idiopathic thrombocytopenic purpura and demonstrated that the complete remission was 66% (2623 patients), while partial remission was observed in 88% of patients (8).…”
Section: 8%)mentioning
confidence: 99%